Michael McCartan’s Books Luminary or Lunatic? - Edward Walsh; Laura P.Z. Izarra (ABEI Journal, 2023)
This is a first attempt to put Fr. Michael John McCartan in the cartography of the Irish chaplains in Argentina under the shadow of Fr. Anthony Fahy, a renowned priest leader of the Irish community in that country. The aim of this article is to motivate historians to look for more information and contextualize McCartan’s actions and impact in the diasporic Irish communities of nineteenth-century Latin America. This is a work-in-progress, and we are indebted to Roberto di Stefano for his generous assistance with this topic and for providing Edward Walsh with a copy of McCartan’s opus in the Mitre Museum, Buenos Aires.